2020
DOI: 10.1017/s1041610220001404
|View full text |Cite
|
Sign up to set email alerts
|

Childhood infectious diseases and old age cognitive functioning: a nationally representative sample of community-dwelling older adults

Abstract: Background: Cumulative evidence suggests that health-related risk factors during midlife and old-age are associated with cognitive impairment. However, studies are needed to clarify the association between early-life risk factors and impaired cognitive functioning to increment existing knowledge. Objective: To examine the association between childhood infectious diseases and late-life cognitive functioning in a nationally representative sample of older adults. Participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Ecological studies have found similar results where childhood infectious diseases have been associated with both positive and negative cognitive outcomes in adulthood [ 42 43 ]. A population based study of healthy adults over 65 also determined that late-life MMSE scores improved as the number of reported childhood diseases (chickenpox, measles and mumps) increased [ 44 ]. Nevertheless, the mechanisms for possible positive outcomes in cognition are not clear [ 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ecological studies have found similar results where childhood infectious diseases have been associated with both positive and negative cognitive outcomes in adulthood [ 42 43 ]. A population based study of healthy adults over 65 also determined that late-life MMSE scores improved as the number of reported childhood diseases (chickenpox, measles and mumps) increased [ 44 ]. Nevertheless, the mechanisms for possible positive outcomes in cognition are not clear [ 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to several epidemiological studies, frequent infections, regardless of etiology, such as pneumoniae (viral or bacterial etiology), urinary tract infections, skin, and soft tissue infections, as well as sepsis from diverse origins, are associated with an increased risk of cognitive decline, vascular dementia, and Alzheimer's disease. Actually, the risk of unspecified dementia would be doubled compared with individuals without a history of severe infectious episodes [4,[26][27][28]. Moreover, a study suggested a risk gradient, with higher infectious burdens associated with higher cognitive risks: an all-cause dementia risk of about 1.4 for a history of one episode of hospital-treated infection, and about 2.5 for two episodes [27].…”
Section: Severe Acute Infections and Their Impact On Cognitionmentioning
confidence: 99%